Build angle effect on 3D-printed dental crowns marginal fit using digital light-processing and stereo-lithography technology: an in vitro study - Engy Farag; Ahmed Sabet; Kamal Ebeid; Omar El Sergany (BMC, 2024)
Abstract Background The effect of 3D printing technology and build angle on the marginal fit of printed crowns is unclear. The objective of this research was to use digital light processing (DLP) and stereo-lithography (SLA)-based 3D printing to construct single restorations with varied build angles and to analyze the crowns' marginal fit. Methods A prepared resin first molar was scanned utilizing an optical scanner. Three build orientations were used to construct the specimens: 0, 45, and 90º. DLP and SLA technology were used to produce the casting patterns. A digital microscope was used to measure the marginal gaps. The effect of build orientation was statistically analyzed by using Two-way ANOVA followed by pair-wise Tukey test. Results Two-way ANOVA revealed a significant effect of printer technology and build angle on the marginal discrepancy of 3D printed crowns (p < 0.001). One-way ANOVA revealed that SLA printers (55.6 [± 13.59]) showed significantly better mean [± SD] marginal discrepancy in µm than DLP printers (72 [± 13.67]) (p < 0.001). Regarding build angle, one-way ANOVA revealed significant differences between the different angles. Tukeys post-hoc test revealed that 0° (48.5 [± 9.04]) had the significantly smallest marginal discrepancy followed by 45° (62.5 [± 8.05]) then 90° (80.5 [± 8.99]) (p < 0.001). Conclusion The build orientation affects the marginal discrepancy of single crowns manufactured utilizing DLP and SLA.